Set up of topical formulations containing sunscreens and the analysis of the stability of these sunscreens - Vieira, Joana Rita Lopes (2019)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014